2013
DOI: 10.1371/journal.pgen.1003989
|View full text |Cite
|
Sign up to set email alerts
|

MAN1B1 Deficiency: An Unexpected CDG-II

Abstract: Congenital disorders of glycosylation (CDG) are a group of rare metabolic diseases, due to impaired protein and lipid glycosylation. In the present study, exome sequencing was used to identify MAN1B1 as the culprit gene in an unsolved CDG-II patient. Subsequently, 6 additional cases with MAN1B1-CDG were found. All individuals presented slight facial dysmorphism, psychomotor retardation and truncal obesity. Generally, MAN1B1 is believed to be an ER resident alpha-1,2-mannosidase acting as a key factor in glycop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 24 publications
(33 reference statements)
5
74
1
Order By: Relevance
“…The formation of a disulfide bond between these residues was demonstrated in the yeast Mns1, which was proposed to stabilize the protein (38). Moreover, R334C and E397K mutations are identified in nonsyndromic autosomal-recessive intellectual disability (NS-ARID) patients (39), and the R334C mutation is also found in the congenital disorders of glycosylation (40). The E397K mutation was found to reduce the ERManI expression, and the R334C mutation was found to reduce the enzyme efficiency by ϳ100% (39).…”
Section: Discussionmentioning
confidence: 99%
“…The formation of a disulfide bond between these residues was demonstrated in the yeast Mns1, which was proposed to stabilize the protein (38). Moreover, R334C and E397K mutations are identified in nonsyndromic autosomal-recessive intellectual disability (NS-ARID) patients (39), and the R334C mutation is also found in the congenital disorders of glycosylation (40). The E397K mutation was found to reduce the ERManI expression, and the R334C mutation was found to reduce the enzyme efficiency by ϳ100% (39).…”
Section: Discussionmentioning
confidence: 99%
“…This mutation was later on identified in two Turkish families and a family of unknown origin with congenital disorders of glycosylation by Rymen et al [62] and Van Scherpenzeel et al [63], as well as in the affected children of a Turkish family with syndromic ID by Hoffjan et al, [64]. They further suggested that this mutation in MAN1B1 leads to a syndromic disorder rather than NS-ARID.…”
Section: Man1b1mentioning
confidence: 93%
“…[1][2][3] (www.lovd.nl/MAN1B1). The standard reference sequence indicating reported variants (ENSG00000177239) and a reference for exon numbering (ENST00000474902) can be found at http://www.…”
Section: Mutational Spectrummentioning
confidence: 99%
“…[1][2][3] The frequency and the prevalence of the disease are not known. Comment: MAN1B1-CDG is an autosomal recessive disorder.…”
Section: Analytical Validationmentioning
confidence: 99%
See 1 more Smart Citation